TO IDENTIFY, EVALUATE, AND ANALYZE THE POSSIBLE DRUG-DRUG INTERACTIONS IN PATIENTS DIAGNOSED AS TYPE 2 DIABETES MELLITUS WITH HYPERTENSION IN A TERTIARY CARE TEACHING HOSPITAL - P LONDHE, SUSHILKUMAR; JOSEPH, ABRAHAM; JOHN, JOSE; PHILIP, KIRAN; PHILIP, LITHIN (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To identify, evaluate, and analyze the possible drug-drug interactions (DDIs) in patients diagnosed as Type 2 diabetes mellitus with hypertension in a tertiary care teaching hospital Davangere. Methods: This prospective interventional study was conducted for a period of 6 months. Data were collected from patients who were prescribed with at least one antidiabetic drug and at least one antihypertensive drug at the same time. Data were analyzed for DDIs by using software Micromedex and other resources. Results were notified to the physicians for modification or alteration in the drug therapy. Results: A total of 150 patients were analyzed out of which, 60.67% were male, and the rest 39.33% were female. In terms of interactions present, 95 (63.33%) prescriptions had one or more interactions. Antihypertensive drugs most frequently seen in prescriptions were diuretics (24.44%). Antidiabetic drugs seen frequently prescribed are biguanides (34.36%). A total of 167 possible DDIs were obtained. Angiotensin-converting enzyme inhibitors were most frequently involved antihypertensive drug in DDIs, with 60 of all possible DDIs identified. Insulin and biguanides were most frequently involved antidiabetic drugs in DDIs, with 58 each of all possible DDIs identified. Most frequently interacting drug pair was insulin + metformin (n=19). Conclusion: For every possible DDIs found in the prescription, the appropriate intervention was advised from the investigator's part as well as provision for a physician to review and initiate modification of his choice. Keywords: Hypertension, Possible drug-drug interaction, Type 2 diabetes mellitus. Â